Physical And Anthropometric Factors Influencing Vertical Jump In Volleyball : Literature Review (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Vertical jump ability is one of the most important performance indicators in volleyball because it directly supports spiking and blocking effectiveness during competition. Optimal jump performance is influenced by various factors, particularly physical and anthropometric characteristics that contribute to explosive movement production and biomechanical efficiency. However, findings regarding the dominant factors affecting vertical jump performance remain varied across previous studies. Therefore, this study aimed to analyze the physical and anthropometric factors influencing vertical jump performance in volleyball athletes through a literature review approach. This study employed a literature review design using secondary data obtained from scientific publications, including reputable national and international journals related to sports science, volleyball performance, physiology, biomechanics, and anthropometry. The data collection process involved identifying, reviewing, and synthesizing relevant research findings published within the last ten years. The selected studies were analyzed descriptively and critically to identify the dominant variables influencing vertical jump performance. The findings revealed that physical factors demonstrated a more dominant influence on vertical jump performance compared to anthropometric factors. Lower limb muscle strength and explosive power consistently showed significant contributions to jump height through neuromuscular force production mechanisms. Maximal strength and training activity also contributed positively, although their effects depended on training specificity and program quality. From an anthropometric perspective, body weight and leg length influenced jump performance through biomechanical mechanisms; however, their effects were generally supportive rather than dominant. In conclusion, vertical jump performance in volleyball is determined by the interaction between physical and anthropometric factors, with neuromuscular capacity serving as the primary determinant. Therefore, volleyball training programs should prioritize explosive power and lower limb strength development supported by optimal body composition management.